Implementasi Peraturan Komisi Pemilihan Umum (PKPU) No 23 Tahun 2018 Pasal 32 Tentang alat Peraga Kampanye Pada Pemilukada di Kecamatan Wonosari Kabupaten Bondowoso Tahun 2019 - Senain Senain; Defri Yudiyanto (ACTON, 2019)
This research focused on how the implementation of Election Commission Regulation No. 23 of 2018 Article 32 on campaign props in the 2019 Pemilukada in Wonosari District Bondowoso Regency. The General Election Commission was national, permanent and independent election management agency. This type of research used qualitative research where researcher used interview, observation, and documentation as the approach study. This study used the theory of democracy, political campaigns, public policy implementation and political communication. The data was collected by library and field study. Regency KPU had applied rules regarding the implementation of campaign props in post-conflict local elections in Bondowoso Regency, but there were still candidates who violated these rules. This was due to the lack of awareness of candidates to obey regulations regarding the installation of campaign props. The results of this study were 1) KPU Bondowoso Regency had implemented the election commission regulation No. 23 of 2018, but there were still many candidates who violated these rules; 2) Problems that becaming obstacles were more progressive decisions from violating political parties that could interfere the political campaign process such as violation of campaign props in trees, worship yards, and government owned buildings, and made these campaign props installation in inapproate places according to the designated places by the KPU.